Investigating Biomass and Water Productivity in the United Arab Emirates: A Case Study of Al Ain Oases - K. Alhebsi; M. ElKamali; S. Albedwawi; K. AlArfati; K. Hussein (ISPRS Annals of the Photogrammetry, Remote Sensing and Spatial Information Sciences)
This study examines the productivity, water dynamics, and environmental factors of oasis ecosystems in Al Ain City, United Arab Emirates. It analyzes Total Biomass Production (TBP), Evapotranspiration (ET), and Net Primary Production (NPP) across different oases and over different seasons. The results reveal significant variations in these parameters, influenced by factors such as oasis size and climatic conditions. Al Ain Oasis exhibited the highest productivity, while smaller oases like Jahili tended to have the lowest TBP and NPP, suggesting potential environmental stresses and lower vegetation density. The study shows seasonal patterns in water demand and ecosystem productivity, with peak ET during summer and higher NPP in winter. These findings underscore the need for adaptive management strategies tailored to each oasis’s unique characteristics. The research provides valuable insights for sustainable practices to enhance oasis resilience and productivity amid limited water resources and climate variability, contributing to the understanding of arid ecosystem dynamics and evidence-based oasis management strategies.